1999
DOI: 10.1002/(sici)1097-4547(19991101)58:3<442::aid-jnr10>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Mexiletine and magnesium independently, but not combined, protect against permanent focal cerebral ischemia in Wistar rats

Abstract: The neuroprotective effect of mexiletine (Mex), a potent Na(+) channel blocker which decreases neuronal energy demands and prevents energy depletion during ischemia, was evaluated in Wistar rats subjected to permanent middle cerebral artery (MCA) occlusion. Postmortem infarct volumes were determined by quantitative image analysis of triphenyltetrazolium (TTC)-stained brain sections. Pretreatment with Mex resulted in a significant infarct volume reduction when administered intraperitoneally, either at the dosag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…The consequence of the energy imbalance is the depletion of ATP, which not only increases the susceptibility of brain tissues to oxidative stress but also triggers the onset of numerous ischemic cascades, leading to neuronal death (Siesjö, 1992; Small and Buchan, 1996; Ames, 2000). One strategy, therefore, to protect the brain against ischemic damage is to improve the energy supply to the tissues “at risk,” and/or to reduce the energy demands of the neuronal tissue (Ames et al, 1995; Maynard et al, 1998, 1999; Ayoub et al, 1999; Lee et al, 1999). It is also presumed that the multifactorial pathogenicity of cerebral ischemia may demand a multimode therapeutic approach.…”
mentioning
confidence: 99%
“…The consequence of the energy imbalance is the depletion of ATP, which not only increases the susceptibility of brain tissues to oxidative stress but also triggers the onset of numerous ischemic cascades, leading to neuronal death (Siesjö, 1992; Small and Buchan, 1996; Ames, 2000). One strategy, therefore, to protect the brain against ischemic damage is to improve the energy supply to the tissues “at risk,” and/or to reduce the energy demands of the neuronal tissue (Ames et al, 1995; Maynard et al, 1998, 1999; Ayoub et al, 1999; Lee et al, 1999). It is also presumed that the multifactorial pathogenicity of cerebral ischemia may demand a multimode therapeutic approach.…”
mentioning
confidence: 99%
“…This was another reason why we have used mexiletine as a pretreatment. 33 Confocal microscopic examination of these groups showed remarkable spatial impairment as detected in three-dimensional neuronal level. Compared with calpain-2 inhibitor group, the mexiletine group showed better cytoskeletal preservation (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Several groups investigated the protective efficacy in experimental studies of permanent focal ischemia and consistently found reduced infarct volumes [1, 2, 20]. Likewise, a reduction of infarct volumes and improved neurological outcome was reported in animal models of temporary ischemia after intravenous administration of magnesium [3, 21].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results in cerebral ischemia [1, 2, 3, 4] and early clinical data in stroke patients [5, 6] supported the idea that magnesium may act as a neuroprotective agent in cerebral ischemia and SAH. In the last two decades, several clinical studies have shown beneficial effects of magnesium in SAH [7, 8, 9, 10, 11, 12, 13, 14].…”
Section: Introductionmentioning
confidence: 94%